PENERAPAN SISTEM AMONG DAN KODRAT ANAK DI SD NEGERI TANDANG 01 KOTA SEMARANG - Angela Astrid Stelladiba Cindy Ayu; Wiwik Widayati; M Maya Mekarsari; Eli Erlinawati; Soedjono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to examine the implementation of the among system and the concept of child nature at SD Negeri Tandang 01 Semarang City. The among system, which is rooted in the educational philosophy of Ki Hajar Dewantara, emphasizes the approach of "Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, Tut Wuri Handayani" in the learning process. Meanwhile, the concept of child nature focuses on the development of the natural potential of each student. Using a descriptive qualitative research method, data were collected through participatory observation, in-depth interviews, and document analysis. The subjects of the study included the principal, teachers, students, and parents of students. The results showed that SD Negeri Tandang 01 has implemented the among system through various student-centered learning activities, examples by teachers, and the provision of responsible freedom to students. The implementation of the concept of child nature can be seen from the school’s efforts to identify and develop students’ individual talents and interests through extracurricular programs and differentiated learning. The main challenges in implementing these two concepts include limited resources and diverse understandings among teaching staff. This study concludes that the implementation of the among system and the nature of children in SD Negeri Tandang 01 has had a positive impact on the academic and character development of students, although it still requires improvement in its implementation.